CREATION SOFTWARE COMPLEX FOR LECTURE MATERIALS CREATION AND SUGGESTS - Polinovskyi , B.B.; Gerasymenko, B.A. (Journal of Information Technologies in Education (ITE), 2010)
The article analyzes weaknesses of existing tools for lecture materials creation and suggests ways to address them. New modular complex architecture is proposed, which will support different types of lecture materials, templates, interactive elements, which can show the dynamic processes, as well as support for lecture material database with searching, sorting, and grouping capabilities.